Setting and Crossing Boundaries: Professionalization of Social Work and Social Work Professionalism - Catrin Heite (Social Work & Society, 2013)
How is a profession distinguished from a non-profession? In what ways is the boundary between profession and non-profession marked, transformed, and dealt with? And how is social work professionalized in these processes of boundary-setting and boundary transfor-mation? In the perspective of Social Work as Working at the Border I address professionaliza-tion, as well as professionalism as boundary-work, boundary-setting and boundary-crossing. This aspect of boundary transformation is discussed in terms of the theory of profession: how does the process of professionalization occur? What is the connection between professionalization, science, politics and the social question? With reference to these questions, a boundary-analytic perspective is outlined in order to review the emergence and development of social work as a profession, and professional ways of handling social inequalities: how is the boundary between profession and non-profession set, secured and transformed? How could this boundary be crossed in processes of professionalization? In the concluding remarks the issue of professionalization as a process will be reversed into the question of professionalism as a mode of practice. Social work will thus be related to a notion of critique, and conceived of as professional boundary-work in the context of social inequality.